Magnetic Materials in Promoting Bone Regeneration - Peng, Jinfeng; Zhao, Jiajia; Long, Yanlin; Xie, Yanling; Nie, Jiaming; Chen, Lili (Frontiers in Materials, 2019)
Strategies to promote bone regeneration have been always the focus of investigations since the skeleton plays important roles like mechanical support, organ protection and mineral homeostasis maintenance in the normal physiological activities of the human body. Magnetic fields have shown to be highly influential in the regeneration process, arousing tremendous interest in utilizing magnetic materials to enhance osteogenesis. In this work, we attempt a more comprehensive and detailed review of magnetic materials in promoting bone regeneration by including not only the mechanisms of bone regeneration, the history and basic concepts of magnetism, but also the types of magnetic materials as well as their influence parameters, designs and fabrication techniques with a focus on their usage in the field of bone regeneration like 3D printed scaffolds and implants. In addition, we provide some possible ideas on the synergistic action between magnetic and other materials on bone tissue. Finally, we propose the development trend of magnetic materials in the field of bone regeneration in the future. There is a huge demand for a more effective and less traumatic way to accelerate bone regeneration of the patients with diseases like fractures, tumors and osteoporosis that cause severe pains, bone loss, limb deformations, and restrictions of mobility. Magnetic materials have substantial potential to be manufactured into novel clinical applications with the ability to increase the bone regeneration efficiency.